2022
DOI: 10.1186/s12879-022-07376-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving access to pre-exposure prophylaxis for adolescent girls and young women: recommendations from healthcare providers in eastern Zimbabwe

Abstract: Background In sub-Saharan Africa, adolescent girls and young women (AGYW) are at high risk of acquiring HIV. A growing number of sub-Saharan African countries are beginning to avail pre-exposure prophylaxis, or PrEP, but with limited success. Unpacking strategies to overcome barriers to the uptake of PrEP is critical to prevent HIV amongst AGYW. This article explores health professionals’ views and recommendations on what is required to increase uptake of PrEP. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 29 publications
4
22
0
Order By: Relevance
“…As identi ed by providers in our interviews, lack of awareness, willingness to prescribe PrEP and con dence as well as biases and stigmatizing attitudes among PrEP providers can represent barriers to PrEP access. This has been similarly found by other studies [14][15][16][17][18][19][20][21], underlining the need for training of providers to provide non-judgmental services, although previous research tended to focus on the US. Providers in our consultations suggested that task sharing with a range of healthcare cadres and lay and peer providers can provide less stigmatizing, more acceptable services and reduce pressure on the health system.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As identi ed by providers in our interviews, lack of awareness, willingness to prescribe PrEP and con dence as well as biases and stigmatizing attitudes among PrEP providers can represent barriers to PrEP access. This has been similarly found by other studies [14][15][16][17][18][19][20][21], underlining the need for training of providers to provide non-judgmental services, although previous research tended to focus on the US. Providers in our consultations suggested that task sharing with a range of healthcare cadres and lay and peer providers can provide less stigmatizing, more acceptable services and reduce pressure on the health system.…”
Section: Discussionsupporting
confidence: 76%
“…Providers have important insights into the realities of their clients' lives and potential barriers and facilitators to PrEP uptake and persistence, and they understand what is needed to effectively implement PrEP services. Providers may also pose barriers to successful programme implementation, for instance due to limited knowledge about service delivery innovations and new products [14][15][16] or biases and stigmatizing attitudes [17][18][19][20][21]. Therefore, understanding provider perspectives can help to inform strategies to strengthen PrEP workforce capacities and thereby further expand access to PrEP services and ensure delivery of comprehensive, non-judgmental, and effective services.…”
Section: Introductionmentioning
confidence: 99%
“…AGYW often experience challenges in accessing pre-exposure prophylaxis (PrEP) and post-exposure prophylaxis (PEP). These challenges emanate from the stigma and discrimination they experience from healthcare workers while trying to access these services, and the lack of financial resources to travel to health centers that offer the services ( Skovdal et al., 2022 ; Ajayi et al., 2020 ). Increasing access to PrEP and PEP among AGYW will help reduce HIV transmission.…”
Section: Strategies To Reduce Hiv Transmission Among Agywmentioning
confidence: 99%
“…Increasing access to PrEP and PEP among AGYW will help reduce HIV transmission. Access can be increased by establishing youth-friendly corners at health facilities, eliminating costs associated with the services, and introducing long-acting formulations, such as the recently approved long-acting injectable cabotegravir for PrEP ( Skovdal et al., 2022 ; Moyo et al., 2022 ).…”
Section: Strategies To Reduce Hiv Transmission Among Agywmentioning
confidence: 99%
“…Nonetheless, in practice, many AGYW face hurdles to their successful engagement with PrEP. Qualitative studies have found HIV and PrEP-related stigma, scepticism towards the use of HIV drugs for prevention, fear of negative reactions from healthcare workers [20,21] and lack of support from relatives, friends and partners, all contribute to low uptake of PrEP [22][23][24]. The role of significant others in shaping AGYW's engagement with PrEP dominates the qualitative literature.…”
Section: Introductionmentioning
confidence: 99%